Affect, Organizational Justice and Innovative Performance - Koon, Saw Wan (2005)
Innovation has received great attention from organizations nowadays. A growing body of research has been carried out to study the antecedents leading to increased innovative performance. This study is intended to contribute to the pool of literature (Malaysian and Western) pertaining to this subject.